URGENSI KEBIJAKAN SKRIPSI BERBAHASA ARAB SEBAGAI MEDIA PENINGKATAN MUTU MAHASISWA JURUSAN PENDIDIKAN BAHASA ARAB - Ammar, Adzfar (Al Mah?ra: Jurnal Pendidikan Bahasa Arab, 2016)
This study aims to determine the factors that cause a student in Arabic Education of UIN Sunan Kalijaga prefer to write the their thesis are in the Indonesian language, the reason is not mandatory thesis in Arabic in the Department of Arabic Language Education of UIN Sunan Kalijaga and formulate a package of measures to improve the quality of graduates by improving the quality essay. This research is descriptive qualitative, is a research field where research in the Department of Arabic Language Education and Teaching Faculty Tarbiyah UIN Sunan Kalijaga Yogyakarta. Methods of data collection in the form of questionnaires and interview guidelines. The source data comes from students who are or have written thesis and the leadership of the Department of Arabic Language Education UIN Sunan Kalijaga as stakeholders. The results showed there are eight factors that cause students of the Department of Arabic Language Education UIN Sunan Kalijaga prefer to write the thesis they are in the Indonesian language, there are four reasons to consider not mandatory thesis in Arabic in the Department of Arabic Language Education UIN Sunan Kalijaga and the third package of measures thesis Arabic for improve the quality of graduates, accompanied by step realization of each activity.